Structure elucidation and immunological activity of a novel exopolysaccharide from Paenibacillus bovis sp. nov BD3526. (15th April 2022) - Zhu, Shiming; Han, Jin; Yan, Zhichao; Wu, Yuze; Zhang, Wenqing; Xia, Wei; Feng, Huafeng
Abstract: A novel exopolysaccharide named BD0.4 was purified from the fermentation broth of Paenibacillus bovis sp. nov BD3526 in wheat bran medium via anion exchange column chromatography. Its fine structure was identified by a variety of physical and chemical methods. BD0.4, with the weight average molecular weight of 376 kDa, consisted of glucuronic acid, glucose and fucose in a molar ratio of 1.58:1:1.66. The backbone included 1, 3-linked Fuc, 1, 3, 4-linked Fuc, 1, 3-linked Glc and 1, 4-linked GlcA residues, with the branching point located at the O4 position of 1, 3, 4-linked Fuc residues, and the branched chain composed of terminal GlcA residues. BD0.4 could improve the phagocytic ability of macrophages and significantly stimulate the secretion of NO, TNF-α, IL-1β and IL-6 from RAW264.7 cells in a dose-dependent manner. BD0.4 could promote the expression of NF-кB and cause nuclear translocation of NF-κB p65, indicating that BD0.4 probably exerted immune activity through the NF-κB signaling pathway. Graphical abstract: Unlabelled Image